O processo inicial de disciplinarização de função na matemática do ensino secundário brasileiro - Braga, Ciro (2003)
The purpose of our study, the disciplinary initial process of the function in the mathematics discipline is linked to the creation, in 1929, of a new school discipline denominated mathematics, resulting from the union of other three: arithmetic, algebra and geometry. This merger was done from an international reference, whose epicenter was in the ideas of the well-known German mathematician Felix Klein, who proposed together with an introduction of Infinitesimal Calculation, a renewal in high school teaching. Such structural transformation in our schooling mathematics was attested, in 1931, for an educational reform Francisco Campos Reform. The main counsellor and articulator of the mathematics teaching transformation in Brazil was Euclides Roxo, who in addition to being a teacher and the principal of Colégio Pedro II in Rio de Janeiro, became the author of several school text-books that had an outstanding role to the function. To his first innovative volumes, Roxo has also taken the conceptions from a North American professor, Ernst Breslich, which are the subject matters in chapter III. In the following chapter, it is done an analysis of the most representative Brazilian school books during the period in which Francisco Campos Reform was in effect. Grounded mainly on the conceptions of the French researcher Chervel about the functioning of the school disciplines and supported on surveys about acceptance of modernizing movement principles in other countries, such as France and Germany, we conclude that it is possible to have a new look through the results of Euclides Roxo s work in introducing function into the contents of our secundary schooling mathematics